Superior Mesenteric Artery Syndrome - Matheos, Efthimiou (S. Karger AG, 2009)
A 63-year-old female presented to our department complaining of epigastric pain, nausea and vomiting. Symptoms started after a significant loss of weight and persisted despite treatment, leading to hospitalization for dehydration and renal failure due to protracted vomiting. During hospitalization, no pathology could be identified and the patient was discharged. Symptoms persisted and she was eventually readmitted. Superior mesenteric artery syndrome was diagnosed based upon clinical suspicion and barium studies. She was subjected to duodenojejunostomy after failure of conservative treatment. Her immediate postoperative course was uneventful and the patient was well during her two-year follow-up. Clinicians should be suspicious of superior mesenteric artery syndrome, albeit rare, and be aware of its treatment, which is either conservative or surgical.